Improving Students’ Writing Skills in Advertising Text Through Audio Visual Media at The Junior High School Level - Garris Pelangi; Piyanart Akkhakraisi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the effectiveness of audio-visual media in improving students’ writing skills in advertisement texts among eighth-grade students at SMPN 87 Jakarta. Methodology: The research employed a quantitative experimental design using a one-group pretest–posttest model. The participants were eighth-grade students selected through random sampling. Data were collected through writing tests focusing on advertisement text composition and analyzed using descriptive statistics and inferential analysis with a paired-sample t-test. Main Findings: The findings indicate a significant improvement in students’ advertisement text writing skills after the implementation of audio-visual media. The mean post-test score (84.56) was higher than the mean pre-test score (71.25), and the calculated t-value (5.46) exceeded the critical t-value (2.04), demonstrating a statistically significant effect. The improvement reflects students’ enhanced ability to develop persuasive content, organize ideas, and apply appropriate language features in advertisement texts. Novelty/Originality of this study: This study contributes to language learning research by providing empirical evidence on the effectiveness of audio-visual media specifically for teaching advertisement text writing at the junior high school level. Unlike studies that focus broadly on multimedia use, this research emphasizes the alignment between instructional media, learning materials, and writing objectives, offering a practical model for integrating audio-visual resources into writing instruction.